Numerical Analysis of Precast Wall Panels with Openings - Ali Joda, Saad Abdulqader; Abdul Samad, Abdul Aziz; Mohamed, Noridah (International Journal of Sustainable Construction Engineering and Technology, 2020)
A finite element (FE) analysis study on precast concrete solid and sandwich wall panels with various openings subjected to axial eccentric load (tw/6) is presented in this paper. Experimental work of nine full-scale and six half-scale wall panels from selected studies were modelled using ABAQUS 6.13 software. The cracking pattern, plastic strain and ultimate load carrying capacity of these FE models were analyzed and comparison from the selected studies was conducted for verification. Results from the FE analysis revealed that the behavior of the wall panels was influenced by the size and location of the openings and its slenderness ratios. From the ultimate load carrying capacity of a solid wall panel and sandwich wall panels with openings, a difference of within 10% of the experimental work from the selected studies was recorded. This observation verifies that ABAQUS finite element software is a reliable and effective technique in determining and establishing the structural behavior of precast wall panels with openings.